Surface tension, spray deposition and volunteer RR© corn control by clethodim and quizalofop associated with adjuvants - Dario, Gustavo [UNESP]; Del Bem, Luciano [UNESP]; Ferrari, Jonas Leandro [UNESP]; da Silva, Flávio Nunes [UNESP]; Raetano, Carlos Gilberto [UNESP] (FapUNIFESP (SciELO), 2023)
Adjuvants mayimprove control efficiency of volunteer RR® corn with ACCase inhibiting herbicides. Thus, the aim of this study was to evaluate the effects of adjuvant addition to the herbicides clethodim and quizalofop, on surface tension, spray deposition and efficiency of volunteer RR® corn control. The surface tension of clethodim (96 g a.i. ha-1) and quizalofop (60 g a.i. ha-1) herbicides with and without a mineral oil, a vegetable oil and an organosilicon adjuvant was evaluated at concentrations of 0.01; 0.05; 0.1; 0.5; 1.0 and 2.0% v v-1. To evaluate deposition and visual control efficiency, the same herbicides associated or not with the mineral oil (0.5% v v-1), the vegetable oil (0.5% v v-1) and the organosilicon adjuvant (0, 05% v v-1) were used. For this, volunteer RR® corn plants were grown in a greenhouse until stage V2-V3. The adjuvants reduced the surface tension of the herbicides clethodim and quizalofop, organosilicon was the most efficient. Adjuvants does not alter spray deposition of herbicides on corn plants. Mineral oil increases potential control of clethodim herbicide and anticipates control with quizalofop herbicide.
Keywords: ACCase inhibitors; mineral oil; surfactant; vegetable oil